Perbandingan Penerapan Evaluasi Pembelajaran Berbasis Digital di Sekolah Dasar: Studi Observasi di SD Temasek Independent School dan SD Binekas Bandung (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to describe and compare the implementation of digital platform-based learning assessments at two elementary schools, namely Temasek Independent School Bandung and Binekas Elementary School Bandung. Advances in information and communication technology have encouraged educational institutions to adopt digital assessment systems to improve efficiency, objectivity, and student participation. This study uses a qualitative descriptive approach through field observation. Data was collected through direct observation of learning activities, presentations from the school, interviews with educators, and documentation. The findings show that both schools have utilized various digital assessment media, such as Learning Management System (LMS), Google Form, Quizizz, Canva, and digital reporting systems. Temasek Independent School emphasizes the use of interactive assessment platforms that support learner-centered learning, while Binekas Bandung Elementary School focuses on systematic monitoring of learning achievements through LMS and digital reporting. Digital platform assessments offer advantages in terms of efficiency, transparency, flexibility, and increased learner motivation, however, there are still obstacles in the form of limited internet access and disparities in digital literacy levels. Overall, the implementation of digital assessment in both schools supports effective learning assessment that is relevant to the demands of 21st-century education.